Microbead‐based synthetic niches for in vitro expansion and differentiation of human naïve B‐cells - Pearlson Prashanth Austin Suthanthiraraj; Sydney Bone; Kyung‐Ho Roh (Bioengineering & Translational Medicine)
Abstract As the prospect of engineering primary B‐cells for cellular therapies in cancer, autoimmune diseases, and infectious diseases grows, there is an increasing demand for robust in vitro culture systems that effectively activate human B‐cells isolated from peripheral blood for consistent and efficient expansion and differentiation into various effector phenotypes. Feeder cell‐based systems have shown promise in providing long‐term signaling for expanding B‐cells in vitro. However, these co‐culture systems necessitate more rigorous downstream processing to prevent various feeder cell‐related contaminations in the final product, which limits their clinical potential. In this study, we introduce a microbead‐based CD40L‐presentation platform for stable and consistent activation of human naïve B‐cells. By employing a completely synthetic in vitro culture approach integrating B‐cell receptor, CD21 co‐receptor, toll‐like receptor (TLR‐9), and cytokine signals, we demonstrate that naïve B‐cells can differentiate into memory B‐cells (IgD‐CD38‐/lo + CD27+) and antibody‐secreting cells (IgD‐CD38++CD27+). During this process, B‐cells underwent up to a 50‐fold expansion, accompanied by isotype class switching and low levels of somatic hypermutation, mimicking physiological events within the germinal center. The reproducible generation of highly expanded and differentiated effector B‐cells from naïve B‐cells of multiple donors positions this feeder‐free in vitro synthetic niche as a promising platform for large‐scale production of effector B‐cell therapeutics.